2011
DOI: 10.1590/s0102-71822011000200003
|View full text |Cite
|
Sign up to set email alerts
|

Julgamento moral sobre pena de morte e redução da maioridade penal

Abstract: O objetivo principal deste trabalho foi investigar o julgamento moral de estudantes do ensino médio e de licenciaturas sobre pena de morte e redução da maioridade penal. Para tanto, utilizou-se como suporte teórico e empírico a tipologia do desenvolvimento moral de Lawrence Kohlberg. Participaram deste estudo 200 estudantes que responderam, além de uma lista que solicitava informações de alguns dos seus dados biodemográficos, a questões relacionadas à pena de morte e à redução da maioridade penal. De um modo g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…This seems to be the same opinion of the parliamentarian PEC authors who, in addition to seeking to reduce the age of criminal majority, proposed that adolescents who commit off enses should undergo psychiatric and psychological evaluation to determine whether they have full capacity to understand their behavior (Corte Real & Conceição, 2013;Silva & Hüning, 2015). Galvão and Camino (2011) showed that the students favoring the reduction of the age of criminal majority justifi ed their opinions based on these same types of arguments.…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…This seems to be the same opinion of the parliamentarian PEC authors who, in addition to seeking to reduce the age of criminal majority, proposed that adolescents who commit off enses should undergo psychiatric and psychological evaluation to determine whether they have full capacity to understand their behavior (Corte Real & Conceição, 2013;Silva & Hüning, 2015). Galvão and Camino (2011) showed that the students favoring the reduction of the age of criminal majority justifi ed their opinions based on these same types of arguments.…”
Section: Resultsmentioning
confidence: 60%
“…27, nº 1, p. 113-126 -March/2019 these, seven were published in scientifi c journals of Psychology, two in journals of Social Communication and two in journals of Political Science. The Psychology studies were concentrated in the following categories: developmental psychology and morality (Cunha, Ropelato, & Alves, 2006;Galvão & Camino, 2011), social psychology (Corte Real & Conceição, 2013;Espíndula et al, 2006;Petry & Nascimento, 2016) and institutional analysis (Scisleski, Bruno, Galeano, Santos, & Silva, 2015;Silva & Hüning, 2015). The articles of Social Communication can be characterized as studies of the editorial organization of newspapers (Dias, 2017) and the interaction between communication and politics (Maia et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations